2018
DOI: 10.1021/acs.inorgchem.8b01479
|View full text |Cite
|
Sign up to set email alerts
|

Nickel-4′-(3,5-dicarboxyphenyl)-2,2′,6′,2″-terpyridine Framework: Efficient Separation of Ethylene from Acetylene/Ethylene Mixtures with a High Productivity

Abstract: A novel compound, [Ni(DCPTP)] (termed Ni-DCPTP), based on the 4'-(3,5-dicarboxyphenyl)-2,2',6',2″-terpyridine (DCPTP) ligand was presented here. Ni-DCPTP has a three-dimensional structure with a ths topology featuring one-dimensional (1D) helical channels. Ni-DCPTP shows an efficient removal of a trace amount of CH from a CH/CH (1/99) mixture with an excellent CH productivity as demonstrated by both the transient breakthrough simulations and breakthrough experiments, generating the polymer-grade CH gas (CH < 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 32 publications
(24 reference statements)
0
11
0
Order By: Relevance
“…The powder X-ray diffraction (PXRD) patterns of the bulk samples of JXNU-10 are close to the simulated ones (Figure S3), suggesting the phase purity of the materials. The thermogravimetric analysis (TGA) results showed that the desolvated frameworks of JXNU-10 can stand up to 440 °C (Figure S4), which is higher than those of the general MOFs including zeolitic imidazolate frameworks (<400 °C), indicating a high thermal stability for these cluster-based RE-MOFs. The high thermal stability of these MOFs should be a result of the robust coordination bonds between the trivalent RE ions and hard Lewis base of oxygen atoms.…”
Section: Resultsmentioning
confidence: 99%
“…The powder X-ray diffraction (PXRD) patterns of the bulk samples of JXNU-10 are close to the simulated ones (Figure S3), suggesting the phase purity of the materials. The thermogravimetric analysis (TGA) results showed that the desolvated frameworks of JXNU-10 can stand up to 440 °C (Figure S4), which is higher than those of the general MOFs including zeolitic imidazolate frameworks (<400 °C), indicating a high thermal stability for these cluster-based RE-MOFs. The high thermal stability of these MOFs should be a result of the robust coordination bonds between the trivalent RE ions and hard Lewis base of oxygen atoms.…”
Section: Resultsmentioning
confidence: 99%
“…Breakthrough Separation Experiments. The breakthrough separation experiments were measured on a homemade apparatus 13 for a 50/50 (v/v) C 2 H 2 /CO 2 mixture at 298 K and 1 atm. A stainlesssteel column with a length of 120 mm and an inner diameter of 3 mm was used.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Gas separation experiments were performed on our previously reported apparatus for gas mixtures. 12 A gas chromatograph with a thermal conductivity detector was used for monitoring the effluent gas from the adsorption column. The separation experiments were carried out at 298 K and 1 atm.…”
Section: ■ Introductionmentioning
confidence: 99%